Efficiency of root length phenotypic index in the evaluation of individual maize plants for aluminum tolerance - Martins, Paulo Roberto (1999)
The objective of this work was to verify the efficiency of the relative seminal root length (RSRL) and net seminal root length (NSRL) as phenotypic indexes for aluminum tolerance in individual maize plants. Seedlings of Al tolerant and susceptible genotypes were grown in nutrient solution containing toxic level of Al for a period of seven days, after which the values of RSRL and NSRL were determined. The results obtained when mean values of RSRL and NSRL were utilized showed that both indexes were able to discriminate tolerant from susceptible maize genotypes. However, when individual values of RSRL and NSRL were utilized, some tolerant plants scored as susceptible ones were observed, showing that the phenotypic evaluation of individual plants by both indexes is subjected to significant errors, mainly in the characterization of susceptible plants. Therefore, in studies for quantitative traits loci (QTLs) mapping for Al tolerance in maize, where these indexes are used, the most appropriate is to use F3 families, where it is possible to obtain mean values for RSRL and NSRL and then utilize these means to represent the phenotypic values of the respective F2 plants.